Pengungkapan Perkara Tindak Pidana Narkotika Di Wilayah Hukum Kepolisian Sektor Concong (Studi Kasus Perkara Nomor: LP/A/01/IX/2025/POLSEK.CONCONG) - Musfidal Arief; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Indragiri Law Review, 2026)
This study examines the process of uncovering a narcotics crime case within the jurisdiction of the Concong Sector Police, with reference to Case File Number: LP/A/01/IX/2025/Polsek.Concong. The research is designed as empirical (sociological) legal research using a statute approach and a case approach, combined with field data obtained from investigators, a suspect, and witnesses at the Concong Sector Police. The findings show that the process of uncovering the narcotics case followed the stages of investigation and inquiry regulated under Law Number 35 of 2009 on Narcotics and the Indonesian Criminal Procedure Code (KUHAP), beginning with the receipt of information, undercover buy and controlled delivery techniques, arrest, search, seizure of evidence, examination of witnesses and the suspect, and coordination with the Public Prosecutor's Office and the Criminal Laboratory. The study also finds that the uncovering of the case faced several obstacles, namely limited investigative personnel and facilities, the closed and clandestine character of narcotics networks, the low willingness of the community to provide information, and the challenge of fulfilling minimum evidentiary standards under Article 183 and Article 184 of the KUHAP. The study recommends strengthening investigative capacity, community-based prevention, and closer inter-agency coordination in order to make the uncovering of narcotics cases in the jurisdiction of the Concong Sector Police more effectivef